2023
DOI: 10.1002/path.6074
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone imbalance drives macrophage infiltration and Spp1/osteopontin+ foam cell differentiation in the prostate

Abstract: Benign prostatic hyperplasia (BPH) occurs progressively with aging in men and drives deteriorating symptoms collectively known as lower urinary tract symptoms (LUTS). Age‐associated changes in circulating steroid hormones, and prostate inflammation have been postulated in the etiology of BPH/LUTS. The link between hormones and inflammation in the development of BPH/LUTS is conflicting because they may occur independently or as sequential steps in disease pathogenesis. This study aimed to decipher the prostatic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 38 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…Our previous study, 15 as well as the current analysis, highlighted that steroid hormone imbalance drives monocyte infiltration to the prostate as well as the translocation of macrophages to the prostate lumen where they differentiate into foam cells. In order to assess how resident prostate cells drive remodeling of the immune environment, we visualized the cytokine expression profile across epithelial, fibroblast and endothelial clusters in T+E2 treated versus control cells (Fig.…”
Section: Steroid Hormone Imbalance Upregulates the Monocyte Attractan...supporting
confidence: 59%
See 4 more Smart Citations
“…Our previous study, 15 as well as the current analysis, highlighted that steroid hormone imbalance drives monocyte infiltration to the prostate as well as the translocation of macrophages to the prostate lumen where they differentiate into foam cells. In order to assess how resident prostate cells drive remodeling of the immune environment, we visualized the cytokine expression profile across epithelial, fibroblast and endothelial clusters in T+E2 treated versus control cells (Fig.…”
Section: Steroid Hormone Imbalance Upregulates the Monocyte Attractan...supporting
confidence: 59%
“…Fibroblast 2 and 3 were mainly localized to the subepithelial region and may potentially be subtypes of the "ductal fibroblasts" identified by Joseph et al 27 Most importantly, we found the highest expression of collagen genes in Fibroblast 3 cells emphasizing that this cell type could be a driver of prostatic fibrosis in the advanced stages of this model. 15 Our future studies will confirm this hypothesis in more chronic stages of the model. The lack of smooth muscle cells in our dataset is potentially due to the digestion protocol selected (cold protease), which will be adjusted in the future to retain these cells.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations